RNA atlas of human bacterial pathogens uncovers stress dynamics linked to infection - Kemal Avican (Nature Portfolio, 2021)
Bacterial stress responses are potential targets for new antimicrobials. Here, Avican et al. present global transcriptomes for 32 bacterial pathogens grown under 11 stress conditions, and identify common and unique regulatory responses, as well as processes participating in different stress responses.